Developing an e-commerce model for Brazil’s animal nutrition in livestock - Perez, Amanda Rolim (2024)
The rise of e-commerce within traditional industries, such as Brazil’s animal nutrition in the livestock sector, offers new growth opportunities and challenges. Despite the sector’s vast economic potential, its integration with online selling remains limited. This research investigates the viability and strategic value of an e-commerce model tailored to Brazil's livestock industry. The primary objective of this study is to assess the adoption of a B2B2C e-commerce model within the livestock sector, aiming to bridge the gap between suppliers, retailers, and farmers. A qualitative, exploratory approach was selected to investigate the complex dynamics of online sales in livestock. By focusing on DSM-Tortuga’s recent business approach, a leading animal nutrition brand, this research seeks to identify factors that could enhance the industry’s adoption of e-commerce while considering the benefits and challenges of integrating digital solutions into a traditionally offline sector. The comparative analysis of AMBEV’s case aims to offer valuable insights for companies, retailers, and farmers considering e-commerce or marketplace models for livestock sales. This study clarifies the potential benefits and challenges of adopting this business approach within Brazil’s animal nutrition in the livestock sector. Findings suggest a strong interest in digital transformation. However, the study also reveals that farmers’ online adoption remains hindered by trust issues and limited online interaction. For successful implementation, tailored support mechanisms, secure payment methods, and a strategic, regionally phased launch are recommended to foster trust and drive the adoption of online sales in Brazil’s livestock sector.